2020
DOI: 10.1002/cam4.2895
|View full text |Cite
|
Sign up to set email alerts
|

Kras mutation correlating with circulating regulatory T cells predicts the prognosis of advanced pancreatic cancer patients

Abstract: Purpose Kras mutation and abnormal immune status are associated with pancreatic cancer development and progression. In this study, we evaluated the Kras mutation status in circulating tumor DNA and circulating T cell subsets in a cohort of advanced pancreatic cancer patients. Methods Samples were retrospectively obtained from a series of 210 pathological advanced pancreatic cancer patients between 2012 and 2014. The Kras mutation status was detected in cell‐free circulating tumor DNA (ctDNA) by ddPCR and circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 33 publications
(73 reference statements)
0
24
0
Order By: Relevance
“…The mutations and concentration levels of ctDNA may be associated with overall survival (OS) and progression-free survival (PFS) in PC patients. Our previous studies demonstrated that K-ras mutations and ERBB2 exon17 mutations detected in ctDNA are significantly associated with OS [ 18 20 ]. However, inconsistent findings have been reported [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mutations and concentration levels of ctDNA may be associated with overall survival (OS) and progression-free survival (PFS) in PC patients. Our previous studies demonstrated that K-ras mutations and ERBB2 exon17 mutations detected in ctDNA are significantly associated with OS [ 18 20 ]. However, inconsistent findings have been reported [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of detectable ctDNA, at baseline or postoperative, in resectable pancreatic cancer patients was significant for the prognosis of disease recurrence and the overall survival. A few relevant studies were based on the analysis of DNA methylation in ctDNA and corroborated the prognostic and diagnostic utility of the ctDNA assay [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. The authors investigated the profile of promoter methylation of BNC1 and ADAMTS1 genes using ctDNA.…”
Section: Ctdna In Pancreatic Cancermentioning
confidence: 99%
“…Previous studies demonstrated that Tregs are increased in many solid tumors [3][4][5][6], as well as hematopoietic malignancies [7][8][9]. In addition, an increased Treg frequency is related to poor prognosis [6,10,11].…”
Section: Introductionmentioning
confidence: 99%